2001
DOI: 10.1097/00007890-200102270-00015
|View full text |Cite
|
Sign up to set email alerts
|

Role of Doppler Echocardiography in the Assessment of Portopulmonary Hypertension in Liver Transplantation Candidates1

Abstract: Doppler echocardiography, and especially the determination of pulmonary acceleration time, is a useful screening method for portopulmonary hypertension in patients with liver cirrhosis who are candidates for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 10 publications
2
60
0
Order By: Relevance
“…Based on the previous results of studies comparing preoperative and peroperative investigations, it has been suggested that, even if not specific, Doppler echocardiography when performed at evaluation is a reliable tool for detecting pulmonary hypertension. 5,6,10 An important finding in this study is that no significant correlation was found between preoperative and peroperative values of MPAP when measured by catheterization in patients who had or did not have portopulmonary hypertension. In contrast to what could be expected, MPAP was on average higher during the first phase of transplantation (under general anesthesia and before incision) than at evaluation in patients without portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Based on the previous results of studies comparing preoperative and peroperative investigations, it has been suggested that, even if not specific, Doppler echocardiography when performed at evaluation is a reliable tool for detecting pulmonary hypertension. 5,6,10 An important finding in this study is that no significant correlation was found between preoperative and peroperative values of MPAP when measured by catheterization in patients who had or did not have portopulmonary hypertension. In contrast to what could be expected, MPAP was on average higher during the first phase of transplantation (under general anesthesia and before incision) than at evaluation in patients without portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 59%
“…It can be suspected that the influence of each of these factors is quite variable from patient to patient and weigh differently according to each case, which could explain, at least in part, that the values of MPAP at the time of evaluation are not significantly correlated to those observed at the time of transplantation. As a consequence, the results of previous studies in which the accuracy of preoperative Doppler echocardiography was assessed by reference to peroperative right heart catheterization, 5,10 even if determined before abdominal incision, have to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 On the other hand, the echocardiographic findings in POPH are typical for pulmonary arterial hypertension (PAH) with a high RVSP ( 40 mm Hg), RV dilatation, and reduced systolic function. 17,18 Although the echocardiographic findings and pathophysiology in HPS and POPH are thought to be mutually exclusive, several cases in the literature have described the possible presence of both entities. [19][20][21][22][23][24][25][26][27][28][29][30] To date, there has been no systematic cTTE study in POPH to evaluate for the coexistence of IPVD findings typical for HPS.…”
mentioning
confidence: 99%